Circular economy for the built environment: A research framework. (1st February 2017) - Pomponi, Francesco; Moncaster, Alice
Abstract: The built environment puts major pressure on the natural environment; its role in transitioning to a circular economy (CE) is therefore fundamental. However, current CE research tends to focus either on the macro-scale, such as eco-parks, or the micro-scale, such as manufactured products, with the risk of ignoring the additional impacts and potentials at the meso-scale of individual buildings. This article sets out to unpack the fundamental defining dimensions of a CE and frame them for CE studies for the built environment. A critical literature review forms the basis for identifying and framing such fundamental dimensions. Our contribution highlights the key roles of interdisciplinary research and of both bottom-up and top-down initiatives in facilitating the transition to 'circular buildings'. The frame for reference has been used to capture current discourse on the sustainability of the built environment and has proved to be a valuable tool to cluster existing initiatives and highlight missing links for interdisciplinary endeavours. The article represents a contribution to the theoretical foundations of CE research in the built environment and a stepping stone to shape future research initiatives. Highlights: Evaluation of the challenges of circular economy studies in the built environment. The current framing of circular economy research is reviewed. Six fundamental dimensions to define circular economy studies are identified and included in a frame of reference. The frame of reference is tested against current initiatives for sustainability in the built environment. Interdisciplinary research is strongly encouraged to exploit the potential of the circular economy concept.